Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/15548627.2019.1596479
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-dependent secretion: mechanism, factors secreted, and disease implications

Abstract: Although best understood as a degradative pathway, recent evidence demonstrates pronounced involvement of the macroautophagic/autophagic molecular machinery in cellular secretion. With either overexpression or inhibition of autophagy mediators, dramatic alterations in the cellular secretory profile occur. This affects secretion of a plethora of factors ranging from cytokines, to granule contents, and even viral particles. Encompassing a wide range of secreted factors, autophagy-dependent secretion is implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 83 publications
1
139
0
Order By: Relevance
“…It has been reported that a wide range of stimuli can activate the NLRP3 inflammasome signaling pathway, which is involved in triggering autophagy-lysosomal dysfunction, and increase the release of proinflammatory factors in microglial cells [53]. Dupont et al demonstrated that autophagy is involved in mediating unconventional secretion of IL-1β [59][60][61]. In contrast, He et al proposed that the inflammasome itself might be one of the likely targets that is negatively controlled by autophagy [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a wide range of stimuli can activate the NLRP3 inflammasome signaling pathway, which is involved in triggering autophagy-lysosomal dysfunction, and increase the release of proinflammatory factors in microglial cells [53]. Dupont et al demonstrated that autophagy is involved in mediating unconventional secretion of IL-1β [59][60][61]. In contrast, He et al proposed that the inflammasome itself might be one of the likely targets that is negatively controlled by autophagy [33].…”
Section: Discussionmentioning
confidence: 99%
“…PG, an important periodontal pathogen, has been reported to activate cellular autophagy, a possible mechanism in inflammatory disease. Multiple groups have observed that the secretion of IL6 depends upon autophagy in some cancers [32,33]. In vitro, when esophageal cancer cells were invaded by PG, autophagy was increased, as was IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indeed indicates that autophagy-related events, in addition to their degradative functions, may participate in unconventional secretion processes, also described as "secretory autophagy" (Claude-Taupin et al, 2017;Ponpuak et al, 2015;Xu et al, 2018). Hence, autophagy can result in secretion of cytosolic proteins or release of sequestered material from cells (Claude-Taupin et al, 2017;New & Thomas, 2019). There exists substantial molecular and functional crosstalk between autophagy and exosome biogenesis (Cadwell & Debnath, 2018;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…enterocolitica not only promotes intracellular survival but also egress of multiplying yersiniae from infected cells. Hence, autophagy can result in secretion of cytosolic proteins or release of sequestered material from cells(Claude-Taupin et al, 2017;New & Thomas, 2019). Liberation of the bacteria is obviously an active process because the fraction of released yersiniae in relation to the total pool of intracellular bacteria was significantly higher in autophagy-competent versus autophagyincompetent, FIP200-negative cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation